1999
DOI: 10.1029/1999jd900475
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic volatile organic compound emissions in central Africa during the Experiment for the Regional Sources and Sinks of Oxidants (EXPRESSO) biomass burning season

Abstract: Abstract. The recent aircraft and ground-based Experiment for the Regional Sources and Sinks of Oxidants (EXPRESSO) campaign in centralModel estimates derived from satellite landscape characterization coupled with leaf enclosure emission measurements conducted during EXPRESSO compared well with these measured fluxes. Isoprene concentrations and fluxes were used to determine the oxidant balance over the forest and savanna. Radiative transfer calculations indicate that the observed strong vertical gradient of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 27 publications
2
37
0
Order By: Relevance
“…The GAW station has made ozone measurements since January 2007 and these data are shown in Campaign daytime (10:00-14:00) average isoprene and total monoterpene fluxes measured at 75 m on the GAW tower were 1.2 and 0.3 mg m −2 h −1 respectively during OP3-I and 2.1 and 0.49 mg m −2 h −1 during OP3-III . These values were comparable to measurements made above regions of the Congo during the EXPRESSO field campaigns (Greenberg et al, 1999;Klinger et al, 1998;Serca et al, 2001) and are somewhat smaller than values reported above regions of the Amazon (Karl et al, 2007;Kuhn et al, 2007). The typical monoterpene to isoprene ratio was between 0.2-0.25, which is within the upper range of ratios reported in other tropical regions .…”
Section: Bukit Atur Measurementssupporting
confidence: 63%
“…The GAW station has made ozone measurements since January 2007 and these data are shown in Campaign daytime (10:00-14:00) average isoprene and total monoterpene fluxes measured at 75 m on the GAW tower were 1.2 and 0.3 mg m −2 h −1 respectively during OP3-I and 2.1 and 0.49 mg m −2 h −1 during OP3-III . These values were comparable to measurements made above regions of the Congo during the EXPRESSO field campaigns (Greenberg et al, 1999;Klinger et al, 1998;Serca et al, 2001) and are somewhat smaller than values reported above regions of the Amazon (Karl et al, 2007;Kuhn et al, 2007). The typical monoterpene to isoprene ratio was between 0.2-0.25, which is within the upper range of ratios reported in other tropical regions .…”
Section: Bukit Atur Measurementssupporting
confidence: 63%
“…Entrainment velocities around 2 cm s −1 estimated from the growth of the planetary boundary layer (PBL) were incorporated as a first order rate constant and constrained by measured ambient MBO concentrations. Limitations associated with photochemical box modelling and the model used here are discussed by , Eisele et al (1997) and Greenberg et al (1999); general aspects of zero-dimensional box modelling can also be found in McKeen et al (1997).…”
Section: Box Model Sensitivity Analysismentioning
confidence: 99%
“…An albedo of 10% was assumed for these calculations and total ozone columns (310-340 Dobson Units) were taken according to data of the NASA Earth Probe TOMS satellite. As in previous applications of the model for planetary boundary layer (PBL) cases (Greenberg et al, 1999b;Karl et al, 2002), entrainment of air during the growth of the PBL was represented as a first-order source or sink for chemical species in the PBL, depending on the concentration difference between background and PBL…”
Section: Photochemical Modelmentioning
confidence: 99%